HUBUNGAN ANTARA KETERAMPILAN BERKOMUNIKASI DAN MINAT BACA DENGAN HASIL BELAJAR BAHASA INGGRIS - Hariyanti Kartika Dewi; Mulyadi Amir (Akademika, 2018)
This study aims to test: 1) Is there a positive and significant correlation between communication skills and English learning outcomes? 2) Is there a positive and significant correlation between reading interest and English learning outcomes? 3) Is there a positive and significant correlation between reading interest and communication skills, along with English learning outcomes? This research uses survey method withcorrelational technique. Target population in this research is all students of class XI SMK in Bekasi city. Samples taken randomly with Slovin formula, obtained 100 respondents.The instrument used to obtain data through Communication Skills (X1), Reading Interests (X2), and English Learning Results (Y) using the Biserial Point formula (rpbis). Criteria used when the biserial point correlation coefficient rtc>rtabel at the reallevel α equals 0.05 or rhitung> 0.361.This research data is collected, processed and analyzed by using descriptive statistic. So the descriptive statistic in question is describe the data for the dependent variable and Independent variable.The conclusions of this study are: 1) There is a positive and significant correlation between communication skills and English learning outcomes. 2) There is a positive and significant correlation between reading interest and English learning outcomes. 3) There is a positive and significantcorrelation between reading interest and communication skills, together with English learning outcomes.